Drafting journalism codes of ethics - Poler Kovačič, Melita (Družboslovne razprave, 2012)
The article reveals the reasons prompting the need for new journalism codes of ethics and the sources upon which they have been founded. Semi-structured interviews with 15 people involved in drafting journalism codes in Slovenia and the Netherlands in the last decade show that some reasons arose from specific national circumstances, while others were common. In Slovenia, foreign codes were the main source. The interviewees claimed that they paid attention to national specifics, yet could not define them. The process was brief, limited to a small group of people and lacked systematic research and wider discussions. In the Netherlands, other codes were consulted, although not copied. The process involved more discussion and reflection. These differences can be interpreted by the different levels of the professionalisation of journalism and some other characteristics of the national contexts.
Keywords: Journalism; Novinarstvo; Journalistic ethics; Novinarska etika; Novinarski kodeks; Journalist code; Ideologija; Ideology; Slovenia; Slovenija; Netherlands; Nizozemska